CIBERJORNALISMO DE PROXIMIDADE E DESENVOLVIMENTO: uma análise sobre três casos do interior paulista - VOLPATO, MARCELO DE OLIVEIRA (2019)
Research about journalistic production processes in the Countryside of São Paulo. The objective was to analyze the current practices of local journalism on the Internet, as well as the transformations and trends verified in the types and specificities of the content produced. The objective was also to apprehend what kind development has been an argumentative focus for such newspapers, as well as to understand if there is a local vocation and which its work strategy. The research starts with the concepts of local, regional and proximity journalism and theoretical approaches to communication for development. The study is also anchored in aspects of the historical-dialectical method and uses multiple case studies as a type of research, focusing on the Correio Popular, from Campinas, Cruzeiro do Sul, from Sorocaba, and Jornal da Cidade, from Bauru. It was also resorted to the bibliographical research, the techniques of semi-structured interviews with the managers of the newspapers and the analysis of the contents published in their websites. Based on its results, it is concluded that these newspapers, in addition to underutilizing the resources and possibilities of the Internet, and reproducing the strategies and culture of printed newspapers, also confront an impasse with the transition from audience to digital, but a difficulty in monetize this new format. Although they have physical proximity to their localities, they do not have provision of services as a priority, establishing weak bonds with audiences and getting much closer to the conceptions of development as modernization.